Antimicrobial susceptibility of Campylobacter jejuni subsp. jejuni assessed by E-test and double dilution agar method in Southern Chile - Fernández H; Mansilla M; González V (Memorias do Instituto Oswaldo Cruz, 2000)
The susceptibility patterns of 108 Campylobacter jejuni subsp. jejuni clinical strains, to six antimicrobial agents was determined by using the E-test and the double dilution agar methods. Using both metods, no strain was found to be resistant to ciprofloxacin, erythromycin and gentamicin, but two (1.8%) were resistant to tetracycline and all to aztreonam. Seven (6.5%) strains were resistant to ampicillin by the E-test and five (4.6%) by the double dilution agar method and by both meyhods. No great discrepancies were observed between both methods.